PENGARUH MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI I PUSKESMAS AMPENAN KOTA MATARAM TAHUN 2024 - Husna, Latifatul; Lale Ajeng Khalifatun Wardani; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Fathurrahman; Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2024)
The determining factors of employee performance include work motivation and leadership style. The problem in thois study is whether ork motivation and leadership style effect employee performance both simultaneously and partially. The purpose of this study is to analyze the influence of work motivation and leadership style on employee performance both simultaneously and partially. This study is a quantitative descriptive study. The population in this study as 84 employees. Respondents were determined using saturated sample collection techniques. The analysis method used multiple linier regression analysis ith SPSS software. The resultss of this study indicate that work motivation and leadership style simultaneously have a significant effect on employee performance. While partially motivation and leadership style have a significant effect on employee performance at the ampenan health center in mataram city.